An Analysis Of Teaching Reading in Recount Text Using Porpe Strategy in Ten-Grade Students of SMA Mardisiswa Semarang in the Academic Year 2023-2024 - Afifah, Nur; Suwarti, Sri; Affini, Laily Nur (Jurnal Penelitian Multidisiplin Ilmu, 2024)
Many students can read English texts with the right pronunciation but do not comprehend the meaning of the text. Thus, their competence to reason in translating the text is still lacking. One of the competencies that must be learned in the English subject curriculum is reading. This study aims to analyze the use of the PORPE strategy in teaching reading recount text for the tenth-grade students of SMA Mardisiswa Semarang in the academic year 2023/2024. This study was conducted by using descriptive qualitative research. The data of this study were collected by using observation and interview to the process of PORPE strategy in teaching reading recount text and students’ self predicted essay questions and answers as supported data/questionnaires. The results of observations, interviews and questionnaires prove that the PORPE strategy has been used in teaching reading recount texts for tenth grade students at Mardisiswa High School. The implementation of the PORPE strategy in teaching recount texts has been effectively structured through five stages. Implementing the PORPE strategy for teaching recount texts faces several barriers. Students struggle to extract main details from text titles due to a lack of effective prediction strategies, hindering their ability to formulate specific and relevant questions.